Preliminary Study on Conversion Model Methods for Hydro-Estimator Rain Rate Integration Time in Malaysia - Hafiz Basarudin,; Noor Hidayah Mohd Yunus,; Nur Auni Izzati Aminudin,; Ling Lloyd,; Chung Boon Kuan,; Aizat Faiz Ramli,; Jahariah Sampe,; Gan Hong Seng, (International Journal of Integrated Engineering, 2024)
This research delves into radio signal propagation, specifically above 10 GHz, where rain-induced signal degradation due to the influence of hydrometeors, particularly rainfall, leads to the phenomenon referred to as rain fade. Current models from the International Telecommunication Union (ITU) have become guides for rain fade prediction, thereby enabling the allocation of appropriate fade margins in the strategic planning of radio networks. However, the existing models have limitations and exhibit a notably confined scope. This research explores an alternative approach using meteorological data, particularly rain radar data, to gain detailed insights into rainfall patterns. The key focus is on harmonizing rainfall rate data into a 1-minute temporal framework suitable for radio network planning. Four methodologies under scrutiny encompass Burgeuno, Joo, Segal, and ITU-R 837 models are examined, as these models have been used in recent research for rain rate integration time conversion. Rigorous testing is conducted using 2020 Hydro-estimator data from various regions of Peninsular Malaysia, Sabah, and Sarawak. By undertaking this exploratory analysis, the paper aspires to not only broaden the comprehension of rain fade dynamics but also to contribute to the refinement of radio network design in Malaysia.